MOTHERHOOD AND FEMALE LABOR FORCE PARTICIPATION REVISITED: EVIDENCE FROM INFERTILITY SHOCKS (Scientific Journal of Actuarial Finance and Accounting, 2025)
Over the last 50 years, the global increase in women’s labor force participation has been accompanied by a substantial decline in fertility rates. While the negative correlation between fertility and female labor market engagement is well-documented, its extent and underlying causes differ across regions. In Central Asia, women’s labor force participation increased modestly from 30% to 34% between 1990 and 2013, whereas fertility rates declined from 3.8 to 2.8 children per woman during the same period. This suggests that factors beyond childbearing may constrain women’s entry into the labor market. This study investigates the causal impact of family size on women’s labor force participation in Uzbekistan and Kazakhstan. Using infertility as an instrumental variable to address endogeneity in fertility decisions, the analysis builds on the methodology proposed by Agüero and Marks (2008). The research hypothesizes that patriarchal norms, particularly prevalent in Uzbekistan, inhibit women’s labor market participation regardless of their fertility status. The findings are expected to contribute to the design of more effective policies aimed at promoting women’s employment in Central Asia.